Ozone Trends during 1979–2019 over Tibetan Plateau Derived from Satellite Observations - Zou, Mingmin; Xiong, Xiaozhen; Wu, Zhaohua; Yu, Chao (Frontiers in Earth Science, 2020)
Ozone (O3) is a very important atmospheric component related to many atmospheric processes. Tibetan Plateau (TP) has played an important role to weather and climate in South Asia and was found to modulate the variation of ozone amount, leading to the ozone low over the TP in both the summer and winter. To better understand the changing trend of ozone, a novel statistic method, i.e. the Ensemble Empirical Mode Decomposition (EEMD) method, is used to analyze the trends of total column O3 (TCO) and the ozone deficit after removing the corresponding zonal mean TCO over the TP. Data of TCO over TP is from satellite observations by OMI/Aura, and for comparison the long-term Merged Ozone Data from NASA is used to analyze the trend of TCO in three latitude zones near TP. In consistent with some other studies, slightly recovery of ozone at 1996-1997 is evident from the zonal mean in three latitude zones between 25oN to 40oN in northern hemisphere, however after 2013 only the north of TP shows an increase trend but the zonal mean between 30oN to 40oN show decrease trends. In contrast, TCO over the TP shows a consistent increase trend from 2004 to 2019, and the ozone deficit over the TP has a rapid increase trend after 2013, with a larger increase trend in the winter season than in the summer. Further analysis to the ozone low events in the winter and summer from 2004 to 2019 shows that the ozone low in May is much deeper and lasts longer than that in the winter. These results show the mechanism of ozone low and its trend in winter is more complex and worthy for more investigation.